Potentiodynamic current/potential characteristics of theoretical mechanisms related to the electrochemical formation and electroreduction of monolayer films on inert electrodes - Tacconi, Norma R. de (1977)
The current/potential curves of various mechanisms related to the electrochemical formation and electroreduction of monolayer films on inert electrodes, involving a single surface covering species and two surface covering species are presented. The potential perturbation functions consist both of single either linear or triangular potential sweeps and of triangular modulated linear potential sweeps. A comparison of the theoretical Eli displays obtained with the different potential perturbation techniques is given for the various reaction pathways presented.